2020
DOI: 10.1111/myc.13098
|View full text |Cite
|
Sign up to set email alerts
|

How can we optimise antifungal use in a solid organ transplant centre? Local epidemiology and antifungal stewardship implementation: A single‐centre study

Abstract: Purpose We aimed to implement and to assess the impact of the antifungal stewardship programme (AFSp) on prescription appropriateness of antifungals, management and outcomes of candidaemia patients, and antifungal consumption and costs at our solid organ transplant (SOT) institute. Methods Local epidemiology of invasive fungal infections (IFIs) from 2009 to 2017 was analysed in order to prepare an effective AFSp, implemented in January 2018. It included suspension of empirical antifungal prescriptions after 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The wrong choice of antifungal agent accounted for most incorrect prescriptions (44%) and that suggests the need for clinicians' education and adherence to guidelines. On the contrary, the European studies reported inappropriate dosing (26.3%–75.9%) as the common error, followed by drug choice (11.9%–30.8%), and indication (6.1%–6.5%) 10,40,41,42,43 . The errors in antifungal prescriptions in Asian countries might be explained by the lack of formal training of clinicians in medical mycology, especially non‐ID physicians and lack of local guidelines 14,44,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wrong choice of antifungal agent accounted for most incorrect prescriptions (44%) and that suggests the need for clinicians' education and adherence to guidelines. On the contrary, the European studies reported inappropriate dosing (26.3%–75.9%) as the common error, followed by drug choice (11.9%–30.8%), and indication (6.1%–6.5%) 10,40,41,42,43 . The errors in antifungal prescriptions in Asian countries might be explained by the lack of formal training of clinicians in medical mycology, especially non‐ID physicians and lack of local guidelines 14,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the European studies reported inappropriate dosing (26.3%-75.9%) as the common error, followed by drug choice (11.9%-30.8%), and indication (6.1%-6.5%). 10,40,41,42,43 The errors in antifungal prescriptions in Asian countries might be explained by the lack of formal training of clinicians in medical mycology, especially non-ID physicians and lack of local guidelines. 14,44,45 It is essential to develop nation-wise manpower development to improve the mycology diagnostic facilities and to formulate hospital-specific management guidelines to overcome the aforementioned shortcomings.…”
Section: (56)mentioning
confidence: 99%
“…AFS differs from antimicrobial stewardship, which conceptually encompasses fungi but primarily addresses bacteria, although research in this field indicates that structured AFS programs are highly needed and show improvement of antifungal therapy 45,46 . There is a particular need for AFS in the SOT setting, where surveys across treating centers in Europe have highlighted potential knowledge gaps and have revealed opportunities for improvement in terms of adequate therapy selection, dosing, duration, and potential drug‐drug interactions 45,47 . Some recent studies have shown the potential benefits of AFS in this setting 48–50 …”
Section: Antifungal Stewardship In the Solid Organ Transplant Settingmentioning
confidence: 99%
“… 45 , 46 There is a particular need for AFS in the SOT setting, where surveys across treating centers in Europe have highlighted potential knowledge gaps and have revealed opportunities for improvement in terms of adequate therapy selection, dosing, duration, and potential drug‐drug interactions. 45 , 47 Some recent studies have shown the potential benefits of AFS in this setting. 48 , 49 , 50…”
Section: Antifungal Stewardship In the Solid Organ Transplant Settingmentioning
confidence: 99%
“…Building on the concept of an ASP “timeout” which has been evaluated for ASPs and supported by the CDC [ 5 ], Mularoni et al performed a multifaceted intervention using a compulsory antifungal “time-out” coupled with ID physician review at 72 h. This intervention was associated with a discontinuation rate of 48% among SOT patients [ 39 ]. The “time-out” prompted a clinical reassessment of the patient, as well as a review of all available microbiological and radiological data.…”
Section: Antifungal Stewardship In Immunocompromised Populationsmentioning
confidence: 99%